2004
DOI: 10.1016/j.chembiol.2004.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Directed Evolution of Epoxide Hydrolase from A. radiobacter toward Higher Enantioselectivity by Error-Prone PCR and DNA Shuffling

Abstract: The enantioselectivity of epoxide hydrolase from Agrobacterium radiobacter (EchA) was improved using error-prone PCR and DNA shuffling. An agar plate assay was used to screen the mutant libraries for activity. Screening for improved enantioselectivity was subsequently done by spectrophotometric progress curve analysis of the conversion of para-nitrophenyl glycidyl ether (pNPGE). Kinetic resolutions showed that eight mutants were obtained with up to 13-fold improved enantioselectivity toward pNPGE and at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
58
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(63 citation statements)
references
References 42 publications
1
58
0
4
Order By: Relevance
“…However, mutations closer to the catalytic core appear to have a greater effect on the selected catalytic activity (30)(31)(32)(33). These residues for mutagenesis may be selected through a random, rational or combined evolutionary approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, mutations closer to the catalytic core appear to have a greater effect on the selected catalytic activity (30)(31)(32)(33). These residues for mutagenesis may be selected through a random, rational or combined evolutionary approach.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent comprehensive study, Aaron et al (12) demonstrated that the evolution of higher activity toward poor substrates did not impair the parental catalytic activity, and, therefore, the evolved enzymes exhibited greater promiscuity. Enzymes evolved for higher substrate enantioselectivity often exhibit lower specific activities toward their new substrates relative to their respective parental enzymes (13)(14)(15). Similarly, the evolution of highly active variants of aspartate aminotransferases capable of accepting branched or aromatic amino acid substrates was accompanied by a relaxation of the substrate selectivity (16,17).…”
mentioning
confidence: 99%
“…Numerous structure-guided and directed evolution strategies have been used in search of enzyme variants that exhibit high catalytic rates with poor or inactive substrates of the parental enzyme (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). As impressive as these successes have been, the engineering of enzymes that exhibit turnover rates and selectivities with new substrates comparable to their natural counterparts has proven quite a challenge, especially when considering those enzymes for which a genetic selection strategy is not possible.…”
mentioning
confidence: 99%
“…The potential for biocatalytic application of epoxide hydrolases was significantly increased with the discovery of microbial epoxide hydrolases (41), which are easier to produce in large quantities. The cloning and overexpression of several enantioselective epoxide hydrolases, e.g., from Agrobacterium radiobacter (35), Aspergillus niger (3), and potato plants (40), not only facilitated large-scale production of these enzymes but also made it possible to improve their biocatalytic properties by site-directed or random mutagenesis (34,36,43).…”
mentioning
confidence: 99%
“…The potential for biocatalytic application of epoxide hydrolases was significantly increased with the discovery of microbial epoxide hydrolases (41), which are easier to produce in large quantities. The cloning and overexpression of several enantioselective epoxide hydrolases, e.g., from Agrobacterium radiobacter (35), Aspergillus niger (3), and potato plants (40), not only facilitated large-scale production of these enzymes but also made it possible to improve their biocatalytic properties by site-directed or random mutagenesis (34,36,43).Since many microbial genome sequences are available in the public domain, it is useful to screen these databases for genes that might encode new enzymes with interesting properties.Novel epoxide hydrolases can be identified by performing a BLAST search of the genomic databases, using amino acid sequences of known epoxide hydrolases as queries. This approach will result in putative epoxide hydrolases but also in amino acid sequences from structurally and mechanistically related enzymes, such as esterases and dehalogenases (33), which can be filtered out using conserved epoxide hydrolase sequence motifs that define the active site (Fig.…”
mentioning
confidence: 99%